Sistem Pendukung Keputusan Rekomendasi Pengangkatan Karyawan Kontrak Menjadi Karyawan Tetap Menerapkan Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) - Laurent Nababan; Roswita Daeli; Dodi Siregar; Erlin Windia Ambarsari; Setiawansyah; Sofiansyah Fadli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
PT. Indoramah Abadi is a national plastic manufacturing company that focuses on the production of mineral water packaging. Because the amount of goods produced is quite large, the company has a large number of employees, including contract employees and permanent employees. However, the large number of employees can cause problems in determining which contract employees will be appointed as permanent employees. This problem occurs because the company does not have objective criteria in selecting permanent employees, causing jealousy among employees. In addition, the calculation process used is still manual and inaccurate, thus affecting employee performance. To overcome these problems, the authors conducted research using the MOORA method. This method is a method that can assist in making decisions by using complex mathematical calculations that can be used to solve problems in conflicting criteria, namely benefits and costs. The results of the study show that alternative A4 with a value of 0.2106 is the highest score. Therefore, it can be concluded that a contract employee named Aksa Alpindo deserves to be appointed as a permanent employee.